STRUCTURAL DA'WAH THROUGH PUBLIC POLICY (ANALYSIS OF DA'WAH ENCOUNTER AND GOVERNMENT LEGITIMACY IN INDONESIA) - Anggara Putra, Riza (UIN Kiai Ageng Muhammad Besari Ponorogo, 2021)
The discussion in this article focuses on the study of structural da'wah in public policy in Indonesia, which is currently widely used by local governments in various regions in Indonesia to improve morale and also campaign for Islamic values in their public policies. The focus of the discussion in this article is first, facts related to structural da'wah in Indonesia. Second, what is the background for the existence of structural da'wah in public policy in Indonesia, third, how is the formulation of structural da'wah in appropriate and good public policies. The fact related to how structural da'wah is mushrooming in Indonesia is that many regions apply structural da'wah in public policy. Various examples of regions in Indonesia that carry out structural da'wah in public policy are one of them in the Bulukumba area of South Sulawesi. As well as in Bandung Regency which has a structural da'wah program with the concept of Bandung Religious, a structural da'wah policy program is also implemented in the Central Java and East Java regions, namely in Jepara and Ponorogo Regencies. The emergence of structural da'wah policies in various regions in Indonesia cannot be separated from the existence of regional autonomy policy authorities. Concerning that local governments can regulate and manage their da'wah policies with their respective social structures. such as the degradation of morals and religious politics of the local government. In formulating the structural da'wah policy, the local government uses various innovations and various alternatives in formulating the da'wah policy. Structural da'wah policies must contain Islamic values and teachings that provide motivation, encouragement and an invitation to the Islamic community to implement and apply Islamic teachings as well as possible. The birth of this policy does not aim to make it an Islamic state and create a pure sharia-based constitution that is beneficial to society. Keywords: Structural Da'wah, Public Policy